Strategi Komunikasi Pengurus Dalam Penegakan Disiplin Kepada Santri Di Pondok Pesantren Madrasatul Qur’an Tebuireng Jombang - Akbar Hafidz; Ahmad Fakhruddin Fajrul Islam (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2023)
Communication as something essential is a very important point for all aspects of human life. In communication there is a communication strategy, such as the communication strategy in enforcing discipline in the Islamic boarding school students of Madrasatul Qur'an Tebuireng. This study aims to examine the communication strategies used by administrators in enforcing discipline against Islamic boarding school students Madrasatul Qur'an Tebuireng in Jombang. This study uses a qualitative method with a descriptive approach. Data collection techniques used in this study were interviews, documentation and observation. The results of this study indicate that the management of Madrasatul Qur'an Tebuireng Islamic Boarding School uses several effective communication strategies in enforcing discipline to students. First, they apply persuasive communication by providing clear explanations and building a shared understanding of the importance of discipline in the life of students. Second, administrators use participatory communication by involving students in making decisions regarding disciplinary rules and sanctions. Third, administrators also use positive communication by giving praise and appreciation to students who show a good level of discipline. Keyword: Management Communication Strategy, Santri Discipline